Interview with the Director General of NASC - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
The National Agricultural Seed Council Director General, Dr ishiak Khalid talks about the strategic partnership between IITA and NASC and how it is impacting seed systems in Nigeria and West Africa.